Biophysical and size-dependent perspectives on plant evolution - Niklas, Karl J (Journal of experimental botany, 2013)
Physical laws and processes have profoundly influenced plant evolution. Their effects are invariably size dependent and thus subject to scaling as well as biophysical analyses even though these effects differ depending upon the fluid (water or air) in which plants evolve. Although organisms cannot obviate the effects of physical laws and processes, the consequences of these effects can be altered by ontogenetic or phylogenetic alterations in geometry, shape, or orientation as well as in body size. These assertions are examined using theoretical insights and empirical data drawn from extant and fossil plants pertinent to four evolutionary transitions: (1) the evolution of multicellularity, (2) the transition from an aquatic to an aerial habitat, (3) the evolution of vascular tissues, and (4) the evolution of secondary growth by the independent acquisition of cambia. This examination shows how physical laws limit phenotypic expression, but how they also simultaneously provide alternative, potentially adaptive possibilities.